Control of singular distributed parabolic systems with discontinuous nonlinearities - Pavlenko, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We present the statement of control problems for singular distributed parabolic systems with discontinuous nonlinearties. Sufficient conditions for the existence of the optimal “control-state” pair are established under the assumption that the set of admissible “control-state” pairs is nonempty. The problem of existence of serniregular solutions is studied for the equation of state of a distributed system. It is not assumed that the nonlinearity of this equation increases sublinearly in the phase variable or possesses a bounded variation on any segment of the straight line.